MuSSE: A Tool to Extract Meta-Data from Game Sprite Sheets Using Blob Detection Algorithm - De Barros Barbosa, Marcelo; De Barros Barbosa, Cecilia; Freitas Barbosa, Andre (Brazilian Symposium on Games and Digital Entertainment (Print), 2015)
This paper introduces a tool to automatically generate meta-data from game sprite sheets. MuSSE is a tool developed to extract XML data from sprite sheet images with non-uniform - multi-sized - sprites. MuSSE (Multi-sized Sprite Sheet meta-data Exporter) is based on a Blob detection algorithm that incorporates a connected-component labeling system. Hence, blobs of arbitrary size can be extracted by adjusting component connectivity parameters. This image detection algorithm defines boundary blobs for each individual sprite in a sprite sheet. Every specific blob defines a sprite characteristic within the sheet: position, name and size, which allows for subsequent data specification for each blob/image. Several examples on real images illustrate the performance of the proposed algorithm and working tool.